2011
DOI: 10.1186/1897-4287-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception among Brazilian individuals with high risk for colorectal cancer and colonoscopy

Abstract: BackgroundRisk perception is considered a motivating factor for adopting preventive behaviors. This study aimed to verify the demographic characteristics and cancer family history that are predictors of risk perception and to verify if risk perception is a predictor of colonoscopy adherence.MethodsIndividuals with a family colorectal cancer history as indicated by a proband with cancer were interviewed by telephone. They responded to a questionnaire covering demographic characteristics, colonoscopy history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
12
1
4
Order By: Relevance
“…In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32). It is pleasing that according to the findings of our study, students under genetic risk show positive behavior for protection from cancer.…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 76%
“…In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32). It is pleasing that according to the findings of our study, students under genetic risk show positive behavior for protection from cancer.…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 76%
“…Karadağ Çaman ve arkadaşlarının (2014) yaptığı çalışmada da ailesinde kanser öyküsü olanlar, bireysel kanser riskini daha yüksek görmektedir (29). Literatürde pek çok çalışma da aile öyküsünün bireylerin risk algısını etkileyen bir faktör olduğunu göstermektedir (30)(31)(32). Bu sonuç bireylerin kendilerini riskli grupta görmelerinin sağlıklı davranışlara yönelmelerinde etkileyici faktör olduğunu göstermektedir.…”
Section: -Serviks Kanserinden Korunma Tutum öLçeği (Skktö)unclassified
“…Bu sonuç bireylerin kendilerini riskli grupta görmelerinin sağlıklı davranışlara yönelmelerinde etkileyici faktör olduğunu göstermektedir. Sağlığı geliştirme alanında çok kullanılan modellerden biri olan 'Sağlık İnanç Modeli'ne göre de algılanan bireysel risk, davranış değişikliğinin önemli belirleyicilerinden biridir (33) Ancak literatürde bireylerin yüksek risk algısının her zaman koruyucu sağlık davranışları ile paralel gitmeyebileceğini gösteren başka çalışmalar da bulunmaktadır (31,34,35).…”
Section: -Serviks Kanserinden Korunma Tutum öLçeği (Skktö)unclassified
“…In a Spanish study carried out in family-risk population [ 95 ], a high subjective perception of risk was an independent predictor for CRC screening (odds ratio = 2.87, 95% confidence interval: 1.10–7.46; P = 0.03). In another study [ 108 ], a higher perception of risk among relatives of patients with CRC increased with the number of relatives with CRC.…”
Section: Factors Impacting Patient Adherencementioning
confidence: 99%